Development of a sky quality imager mobile app for on-site measurement of night sky brightness - Ng, Kai Xiang (Nanyang Technological University, 2024)
Light pollution is a problem that disrupts ecosystems, disrupts astronomical studies, and has the potential to have negative impacts on human health. To raise awareness as well as assist urban planners in city planning, highly accessible tools to quantify light pollution are indispensable. This paper highlights the development of an Android application designed to achieve the primary objective of measuring sky brightness. The application utilises the smartphone camera, as well as image processing techniques to derive the sky brightness in apparent magnitude per square arcsecond. The Android application consists of 4 main components: Pixel Resolution, Adaptive Thresholding for addition of data points, Graph Plotting and the night Sky Analysis. The pixel resolution focuses on determining arcseconds per pixel, which will help determine the night sky angular size in square arcseconds. Adaptive Thresholding aims to accurately capture the star’s pixel value with localised thresholding. Graph plotting is important as the calibration curve maps out the pixel value of the celestial objects against their corresponding known apparent magnitude. The night sky analyser makes use of both the pixel resolution and the apparent magnitude from the calibration curve to determine the sky brightness in apparent magnitude per square arcsecond.